A Protocol for Dual Calcium-Voltage Optical Mapping in Murine Sinoatrial Preparation With Optogenetic Pacing - Dong, Ruirui; Mu-u-min, Razik; Reith, Alastair J. M.; O’Shea, Christopher; He, Shicheng; Duan, Kaizhong; Kou, Kun; Grassam-Rowe, Alexander; Tan, Xiaoqiu; Pavlovic, Davor; Ou, Xianhong; Lei, Ming (Frontiers in Physiology, 2019)
Among the animal models for studying the molecular basis of atrial and sinoatrial node (SAN) biology and disease, the mouse is a widely-used species due to its feasibility for genetic modifications in genes encoding ion channels or calcium handling and signalling proteins in the heart. It is therefore highly valuable to develop robust methodologies for studying SAN and atrial electrophysiological function in this species. Here, we describe a protocol for performing dual calcium-voltage optical mapping on mouse sinoatrial preparation (SAP), in combination with optogenetic approach, for studying SAP membrane potential, intracellular Ca2+ transients and pacemaker activity. The protocol includes the details for preparing intact SAP, robust tissue dual dyes loading, light programmed pacing and high-resolution optical mapping. Our protocol provides an example of the use of combination of optogenetic and optical mapping techniques for investigating SAP membrane potential and intracellular Ca2+ transients and pacemaker activity with high temporal and spatial resolution in specific cardiac tissues. Thus our protocol provides a useful tool for studying SAP physiology and pathophysiology in mice.